Drive Campaigns : "Anti-Sharing Images/Photographs Harassing Women On Instant Messaging Apps Phone Visting" - Winny Gunarti; Widya Wardani (ADI Journal on Recent Innovation, 2020)
The presence of cross-platformmessaging apps on smartphone allows people to instantlyshare information and images/photos. However, the development of this informationtechnology also opens opportunities for the spread of gender-based of images/photos thattend to harass women. The act of harassing women through images/photos, whetherproducing or sharing them can be categorized as a violation of the law, as regulated in Law ofthe Republic of Indonesia No. 7 year 1984 on the Ratification of the Convention on theElimination of All Forms of Discrimination against Women. This study focuses on theimportance of campaign of"Anti-sharing images/ photos that harassed women in instantmessaging apps on smartphone? as a form of social and cultural responsibility in thecommunity. Qualitatively, the discussion uses the theory of design sociology as a solution tosolve problems through campaign media. The results of this study discussions are expectedto build public awareness to stop sharing habits or create images /photos that harass women,and invite people to jointly fight it.